Cohabitation and the evolving nature of intimate and family relationships - Blair, Sampson Lee; Zhang, Yongjun (Contemporary perspectives on family research ;, 2023)
In societies around the globe, couples are increasingly opting to live together without going through the formal and legal complications of marriage. Given the tremendous diversity in cohabiting couples, as well as the increasing prominence of this form of intimate relationships, Cohabitation and the Evolving Nature of Intimate and Family Relationships provides a more thorough comprehension of the structures, effects, and intimate practice of cohabitation around the world. As a richly edited collection, the chapters delve into a wide array of topics including transitions into cohabitation, parenting and parental roles, division of domestic labor among cohabitors, sharing of economic resources, elderly cohabitors, legal complications of cohabitation, intimate partner violence, interconnections between cohabitation and marriage, sex and sexuality, assortative mating among cohabiting partners, premarital cohabitation and its consequences, relationship dissolution, gender ideologies, changing patterns of cohabitation, cohabitation and remarriage, and parental cohabitation and child development, among others. This is compelling reading for scholars of family research for better comprehending the structural, affectional, and other characteristics of cohabitation around the world.